DOCUMENTING ARCHITECTURAL HERITAGE IN BAHIA, BRAZIL, USING SPHERICAL PHOTOGRAMMETRY - A. L. De Amorim (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
The Cultural Heritage disappears at a rate higher than we are able, not only, to restore but also to document: human and natural factors, negligence or worst, deliberate demolitions put in danger the collective Architectural Heritage (AH). According to CIPA statements, the recording is important and has to follow some guidelines. The Architectural and Urban Heritage data have to be historically related, critically assessed and analyzed, before to be organized according to a thematic structure and become available for further uses. This paper shows the experiences developed by the Laboratory of Computer Graphics applied to Architecture and Design (LCAD), at the Architecture School of the Federal University of Bahia (FAUFBA), Brazil, in cooperation with the Università Politecnica delle Marche (UNIVPM, DICEA Department), Italy, in documenting architectural heritage. The research set up now has been carried out in the historical sites of Bahia, as Pelourinho neighborhood, a World Heritage by UNESCO. Other historical sites are in the plan of this survey, like the cities of Lençóis and Mucugê in Chapada Diamantina region. The aim is to build a technological platform based on low cost digital technologies and open source tools, such as Panoramic Spherical Photogrammetry, Spatial Database, Geographic Information Systems, Three-dimensional Geometric Modeling, CAD technology, for the collection, validation and dissemination of AH.